2016
DOI: 10.1073/pnas.1612820113
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of ectodermal and mesodermal gene regulatory network linkages in early development of sea urchins

Abstract: Developmental gene regulatory networks (GRNs) are assemblages of gene regulatory interactions that direct ontogeny of animal body plans. Studies of GRNs operating in the early development of euechinoid sea urchins have revealed that little appreciable change has occurred since their divergence ∼90 million years ago (mya). These observations suggest that strong conservation of GRN architecture was maintained in early development of the sea urchin lineage. Testing whether this holds for all sea urchins necessita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…In E. tribuloides, only one NSM domain forms before gastrulation, and this co-expresses Et-myc, Et-gcm, Et-gatae and Et-ets1/2. The subdivision of NSM cell fates was shown to occur shortly after the onset of gastrulation (Erkenbrack, 2016). In the endoderm, both species express gatae, myc, blimp1 and foxa in AE, and bra, hox11/ 13b, eve and wnt8 in PE (Peter and Davidson, 2011b).…”
Section: Conserved Expression Of Regulatory Genes In Endomesodermal Cmentioning
confidence: 99%
“…In E. tribuloides, only one NSM domain forms before gastrulation, and this co-expresses Et-myc, Et-gcm, Et-gatae and Et-ets1/2. The subdivision of NSM cell fates was shown to occur shortly after the onset of gastrulation (Erkenbrack, 2016). In the endoderm, both species express gatae, myc, blimp1 and foxa in AE, and bra, hox11/ 13b, eve and wnt8 in PE (Peter and Davidson, 2011b).…”
Section: Conserved Expression Of Regulatory Genes In Endomesodermal Cmentioning
confidence: 99%
“…In contrast, cidaroids have shown remarkable morphological conservation, and the earliest fossil cidaroids are almost morphologically identical to cidaroids living in the oceans today (20,21). Comparative studies of GRN architecture between cidaroids and euechinoids have revealed extensive differences in the wiring of their early developmental GRNs (8,22,23), and have served to inform our understanding of the genomic underpinning of the myriad morphological differences in their embryonic and larval development (24,25).…”
mentioning
confidence: 99%
“…The variance in our data for VEGF transcripts around the onset of transcription likely reflects both the low abundance of this transcript and the sensitivity of our qPCR assay. This temporal sequence in E. tribuloides is similar to other NODAL‐responsive regulatory genes and is 3–4 hr removed from the onset of nodal —similar to chordin (Erkenbrack, ). Shortly after gastrulation commenced at 24 hpf, vegf signaling was not detected by WMISH, which is likely due to low levels of mRNA product (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Embryos were cultured in controlled conditions at 22°C. Probe preparation, embryo fixation, whole‐mount in situ hybridization (WMISH) and quantification of RNA transcript abundance by quantitative PCR (qPCR) were all conducted as previously described (Erkenbrack and Davidson, ; Erkenbrack, ; Erkenbrack et al., ). In S. purpuratus , there are three annotated VEGF ligands (VEGF, VEGF2, and VEGF3) and two annotated VEGF receptors (VEGFR‐7‐IG and VEGFR‐10‐IG) (Duloquin et al., ).…”
Section: Methodsmentioning
confidence: 99%